The Law for The Perpetrator of The Great Sin According to Kharijite Sects (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2023)
This research deals with the issue of the perpetrator of major sins, which is one of the great issues that arose the dispute of Islamic teams since the early era of Islam, after the killing of Othman bin Affan, and then appeared in the era of the fourth caliph Imam Ali, , after the arbitration order, so the Kharijites band went to the infidelity of the perpetrator of the great and they said his immortality in the fire, so they disbelieved some of the companions of the Messenger of God. To reach the desired results, the researcher will rely on dealing with this research on the analytical method, which is to present the views of the Kharijites and the views of the Sunnis in the judgment of the perpetrator of the large. The results of the research are that the Kharijites were the first to create the idea of atonement for the perpetrator of the great after the arbitration order between Ali and Muawiyah.